GUARDIANS OF HEALTH: STATISTICAL APPROACHES TO EPIDEMIOLOGY FOR TRACKING AND CONTROLLING DISEASES - L. O. Mallasiy, (Chelonian Research Foundation, 2022)
In recent years, global public health has confronted challenges from emerging infectious diseases, necessitating effective tracking and control measures. Epidemiology, as the study of health-related event distribution and determinants within populations, plays a pivotal role in disease management. The objectives of this study are to review and analyze current statistical approaches in epidemiology for disease tracking and control, identify gaps and limitations in existing methodologies, and propose innovations to enhance disease surveillance and control efforts. This research employs a comparative study design, analyzing the effectiveness of various statistical approaches in epidemiology for disease tracking and control using retrospective analysis of diverse datasets from Germany over a five-year period (2016-2020). The descriptive epidemiology analysis revealed the prevalence and temporal trends of different diseases, highlighting the need for targeted interventions. The analytical epidemiology studies, including the case-control and cohort studies, identified important risk factors for respiratory infections and demonstrated the effectiveness of a vaccination program in reducing the incidence of vector-borne diseases. The spatial epidemiology analysis accurately identified high-risk areas for gastrointestinal infections, aiding in the implementation of focused surveillance and control strategies. The time series analysis successfully detected disease outbreaks and provided guidance for timely interventions. These findings contribute valuable insights to the field of epidemiology and provide a basis for evidence-based public health strategies and interventions in Germany. Keywords: Epidemiology, statistical approaches, disease tracking, control measure, spatial epidemiology, gastrointestinal infections, time series analysis